Pengukuran Kualitas Website E-Learning MAN Sidoarjo menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) - Delfitri Nanda Irawan; Buce Trias Hanggara; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
MAN Sidoarjo is the only Madrasah Aliyah Negeri in Sidoarjo Regency that utilizes the e-learning website as a medium to support online learning activities for the success of their student learning activities even from home. As the only public madrasah aliyah in Sidoarjo, it is important to maintain the quality of quality education services as a form of supervision of education quality assurance so that evaluation or measurement of services is needed which until now has never been implemented. There were several complaints submitted by students regarding the e-learning website such as an unattractive appearance, providing less up-to-date information, to the layout of information that confuses users. The complaints that have been submitted have encouraged researchers to research the quality of e-learning website services. The quality of e-learning website services is measured using Webqual 4.0 and Importance and Performance Analysis (IPA). Webqual 4.0 can be used to determine whether the quality of the current website performance has met the expectations of users based on the three dimensions of Webqual 4.0 including the dimensions of usability, information quality, and service interaction quality. Then the Importance and Performance Analysis (IPA) method is used to determine the priority of improvement on which attributes and dimensions are the main focus for improvement. The measurement results from 102 respondents found that 5 statement attributes that are included in the priority level for major improvements are clear and easy to understand interactions, easy to navigate, have an attractive and attractive appearance, provide sufficient detailed information, and appropriate layout information. Then 5 statement attributes are included in the low priority level, namely, the information provided can increase knowledge, the layout of the information is arranged correctly, the information is up to date, it is easy to attract the attention of students and communicate with the teacher. For other attributes, they already have a good level of performance to have excessive-quality so that it is sufficient to maintain the quality service provided.